Effect of Chronic Melatonin Supplementation on Fitness Profile Parameters in Sedentary Young Men of Kolkata, India - Basu, Sohini; Majee, Anindita Mandal; Bandyopadhyay, Debasish; Bandyopadhyay, Amit (British Journal of Healthcare and Medical Research, 2024)
Purpose: Melatonin, a safe and pleotropic biomolecule might have ergogenic benefits beyond its antioxidant and chronobiotic properties to combat deleterious health consequences of sedentary lifestyle. Present study was aimed to investigate the comparative fitness profile analysis following chronic melatonin supplementation in young, untrained sedentary male subjects in contrast to placebo. Methods: A single blinded randomized controlled trial was conducted with the melatonin group (MG) (n=14) and placebo group (PG) (n=14). Melatonin at a dose of 3mg/day, 30-60 mins before bed time was administered nocturnally to the MG for 4 weeks. All the measurements were taken weekly in the morning. Fitness profile broadly consisted of a battery of standardized physical and physiological tests (aerobic, anaerobic and motor fitness parameters). Statistical analyses comprised of repeated measures ANOVA with the level of significance set at p<0.05. Results: In comparison to PG, a significant treatment effect was noted for vertical jump test (VJT) score and handgrip endurance, both higher in MG. Further, a significant time effect was observed with greater handgrip strengths (right and left hand), handgrip endurance, flexibility, VJT score, balance and lower blood pressure (systolic and diastolic) in MG. Conclusion: Chronic nocturnal melatonin administration is capable of improving certain fitness performances.